Perception of partisans toward democratic practice and the appointment of Prime Minister of Jordan - Al-Majali, Jehad Mohammad Khazer (2021)
The Jordanian constitution gives the absolute power to the King to appoint the prime minister without referring to the will of people in Jordan. This King-based selection of the prime minister is however thought to harm the democratic practice and the future of the democratization process in Jordan. As such, this study aims to identify the Jordanian partisans’ perception of (i) the concept of democracy, (ii) the democracy practice in Jordan, and (iii) the appointment of the prime minister by the King. A survey questionnaire using a quantitative design was conducted and a total of 380 partisans took part in the study. The gathered data of the study was analyzed using descriptive statistics and a one-way ANOVA. The results of the analysis revealed that the participants were less clear in their stance of the notion of democracy. The democratic practice in Jordan was also influenced by some obstacles including tribalism, which has a great influence on the parties’ activities and elections. Giving the King the full constitutional right to appoint the prime minister was also considered the most significant factor that hinders the democratization process in Jordan. The Jordanian partisans seem to be in support of the view that taking people’s demands into consideration is the most important factor that should be considered by the King in appointing the prime minister. In discussing the differences between the political factions toward the current democratic practice in Jordan and the appointment of the prime minister, the results showed that both the right wing and left wing were dissatisfied with the current democratic practice in Jordan, whereas the moderates seemed to be neutral in their stance. These results together can provide insights about the democratization process, and the factors hindering this process in Jordan.